Death in the woods - Anderson, Sherwood, 1876-1941.
Typescript and galley proof of Death in the woods.
In part, typewritten transcript.
Author.
Collection material in English.
Forms part of: Miscellaneous Manuscripts collection.
Keywords: Authors